2019
DOI: 10.1101/535591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genetic structure of the European black pine (Pinus nigraArnold) is shaped by its recent Holocene demographic history

Abstract: Highlights• The European black pine, Pinus nigra (Arnold), has a weak spatial genetic structure.• Gene flow among populations is frequent and populations are often of admixed origin.• Current genealogies result from recent, late Pleistocene or Holocene events. 2 0• Seven modern genetic lineages emerged from divergence and demographic contractions.• These seven lineages warrant a revision of subspecies taxonomic nomenclature. Abstract 2 5Fragmentation acting over geological times confers wide, biogeographical s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…According to Giovannelli et al (2017), such SSR markers are highly informative and valuable for population genetic studies and can be interesting to resolve the complex taxonomy of the P. nigra. Giovannelli et al (2019) recently reported the need for revising the infraspecific taxonomy of this pine species based on the integration of molecular data with its demographic history resulting from geological events. Regarding the wide and patchy distribution of P. nigra, it was expected a strong genetic differentiation among populations and a low within-population genetic diversity (Giovannelli et al 2019;Scotti-Saintagne et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Giovannelli et al (2017), such SSR markers are highly informative and valuable for population genetic studies and can be interesting to resolve the complex taxonomy of the P. nigra. Giovannelli et al (2019) recently reported the need for revising the infraspecific taxonomy of this pine species based on the integration of molecular data with its demographic history resulting from geological events. Regarding the wide and patchy distribution of P. nigra, it was expected a strong genetic differentiation among populations and a low within-population genetic diversity (Giovannelli et al 2019;Scotti-Saintagne et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Giovannelli et al (2019) recently reported the need for revising the infraspecific taxonomy of this pine species based on the integration of molecular data with its demographic history resulting from geological events. Regarding the wide and patchy distribution of P. nigra, it was expected a strong genetic differentiation among populations and a low within-population genetic diversity (Giovannelli et al 2019;Scotti-Saintagne et al 2019). However, these authors reported a weak genetic spatial structure probably resulting from the fragmentation of an ancestral population at the late Pleistocene or early Holocene into six to seven genetic lineages with high gene flow among them, actively contributing for admixture (Giovannelli et al 2019;Scotti-Saintagne et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations